Anorectal Malformation With Fistel - Anjani Berliana Alitu; Berry Erida Hasbi; Fitriya Idrus; Muhammad Fakhri Rumi; Floria Eva (Jurnal EduHealth, 2024)
Anorectal malformation (MAR) with fistula is a congenital abnormality in which patients do not have an anus and the formation of a fistula. In men, the types of fistula are rectovesica fistula, rectourethra, and perineal fistula. Meanwhile, in women, the types of fistula are rectovaginal fistula, rectovestibular fistula, cloaca and perineal fistula. The diagnosis is made by the presence of meconium in the urine. On physical examination, a flat perineum was found, there was no anal dimple and there was meconium in the perineum. The treatment is colostomy in cases of high fistula then Posterior Sagittal Anorectoplasty (PSARP) and fistulectomy, while in low fistula cases PSARP and fistulectomy are immediately performed.